Factors affecting the separation of organic compounds by gas liquid chromatography - Hagens, Rodger Graham Robertson (Department of Chemistry, 2016)
The objects of this thesis have been threefold. In the first place it has been an investigation of the factors which influence retention time in an attempt to predict the retentions of new compounds. Secondly it has been an investigation into the conditions for the best separation of diastereoisomers, and thirdly it has been an application of gas chromatography in the study of the forces of intermolecular interaction in solution. To carry out these investigations, the retention times of twenty five monofunctional and bifunctional compounds have been determined on four stationary liquids at 130°C. It was found that by dividing the retention time of a solute by that of a hypothetical normal hydrocarbon of the same molar volume of the solute, a functional group constant was obtained. By means of this constant, termed the Group Retention Factor, it was found that it is possible to predict the retention of bifunctional compounds. The separation of diastereoisomeric pairs is discussed in terms of the Group Retention Factors of the functional groups on the diastereomers. The molar volume is also utilized in order to develop an equation by means of which the ratio of retention times on two solvents can be related to the forces of interaction between solute and solvent.